Preface [to] RoboCup 2007: Robot Soccer World Cup XI - Visser, Ubbo (2008)
[Excerpt] The 11th RoboCup International Symposium was held during July 9–10, 2007 at the Fox Theatre in Atlanta, GA, immediately after the 2007 Soccer, Rescue and Junior Competitions. The RoboCup community has observed an increasing interest from other communities over the past few years, e.g., the robotics community.RoboCupisseenasasigniﬁcantapproachtotheevaluationofnewlydeveloped methods to many diﬃcult problems in robotics. Atlanta was also the location of a RoboCup@Space demonstration, which reﬂected the role of AI and robotics in space exploration. Prior to the symposium, space agencies had expressed an interest in cooperating with RoboCup. A ﬁrst step in this direction was a successful demonstration at RoboCup 2007, which was accompanied with aninvitedtalkgivenbyaleadingscientistfromtheJapanAerospaceExploration Agency JAXA. [...]